Interpreting Chopin : Analysis and Performance. - Hood, Alison (Ashgate Publishing Ltd, 2014)
Alison Hood combines significant aspects of current analytical approaches and applies that unique synthetic method to selected works by Chopin. The specific combination of five aspects distinguishes Hood's method from previous analytical approaches. These five methods are attention to the rhythms created by pitch events on all structural levels; a detailed accounting of the musical surface; 'strict use' of analytical notation; a continual concern with 'strategies' or 'premises'; and an exploration of how recorded performances might be viewed in terms of analytical decisions, or might even shap.